2018
DOI: 10.1016/j.jcmg.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Incremental Prognostic Value of Cardiovascular Magnetic Resonance After ST-Segment Elevation Myocardial Infarction

Abstract: Early post-infarction CMR-based MVO is a strong independent prognosticator in revascularized STEMI patients. Remarkably, MVO extent ≥2.6% of LV improved long-term risk stratification over traditional outcome predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 33 publications
2
45
1
2
Order By: Relevance
“…Similar findings were reported from a multicenter registry including 810 revascularized STEMI patients [97]. MVO was associated with MACE in all multivariate models irrespective of whether it was entered as a dichotomous, continuous, or optimal cutoff variable [97]. In contrast, IS lost its prognostic relevance when corrected for MVO once again [97].…”
Section: Microvascular Injurysupporting
confidence: 80%
See 2 more Smart Citations
“…Similar findings were reported from a multicenter registry including 810 revascularized STEMI patients [97]. MVO was associated with MACE in all multivariate models irrespective of whether it was entered as a dichotomous, continuous, or optimal cutoff variable [97]. In contrast, IS lost its prognostic relevance when corrected for MVO once again [97].…”
Section: Microvascular Injurysupporting
confidence: 80%
“…Regenfus et al showed that the extent of MVO was the strongest prognostic factor for six-year MACE rates in 245 STEMI patients [96]. Similar findings were reported from a multicenter registry including 810 revascularized STEMI patients [97]. MVO was associated with MACE in all multivariate models irrespective of whether it was entered as a dichotomous, continuous, or optimal cutoff variable [97].…”
Section: Microvascular Injurysupporting
confidence: 53%
See 1 more Smart Citation
“…There was a graded reduction in event-free survival in patients with MI size <25% of the LV, with and without microvascular obstruction, and those with MI size >25% of the LV, with and without microvascular obstruction. The prognostic value of microvascular obstruction over MI size for mortality and hospitalization for heart failure was recently confirmed by de Waha and colleagues 51 in a pooled analysis of patient-level data from 7 randomized controlled trials (n=1688) at 1 year and by Symons and colleagues 62 in a longitudinal study of 810 patients following a median follow-up of 5.5 years.…”
Section: Recent Advances In the Role Of Cmr In Reperfused Stemi Patientsmentioning
confidence: 83%
“…Symons et al demonstrated that early post-infarction CMR-based MVO was a strong independent predictor of MACE in reperfused STEMI patients at long-term follow-up. Remarkably, MVO extent ≥2.6% of LV was the strongest independent predictor of death and heart failure hospitalization, overriding the prognostic performance of traditional outcome predictors and leading to better long-term risk stratification [39].…”
Section: Cardiac Magnetic Resonancementioning
confidence: 95%